Peran Media Sosial dalam Komunikasi Internal Organisasi Studi Kasus Organisasi Mahasiswa di UIN SMH Banten - Erfan Maulana (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2025)
This research examines the role of social media as a means of internal communication within student organizations at UIN Sultan Maulana Hasanuddin Banten. Using a case study approach, the research explores how platforms such as WhatsApp, Instagram, and Facebook are utilized for activity coordination, information dissemination, and strengthening relationships among members. The results indicate that social media provides advantages in terms of speed, accessibility, and interactivity of communication, as well as facilitating the storage of important organizational information. However, challenges exist in the form of information overload, communication ethics issues, digital access disparities, and declining quality of face-to-face interactions. The research also identifies effective strategies for managing internal communication through social media, including the development of communication guidelines, member training, appropriate platform selection, communication scheduling, continuous evaluation, and integration with offline communication methods. The research findings contribute to the development of adaptive organizational communication models in the digital era for student organizations.